Human Vs Robot: the battle for the workplace: a case study of Lembaga Tabung Haji, Parit Raja branch - Abu Seman, Noor Aslinda; Fernandez, Dahlia (Penerbit UTHM, 2020)
The advancement of new accounting system had aroused from the growth in information technology. These development had led to new term namely accounting information system which benefits to minimize time, cost, and money by providing more add-value and enhanced transactions and communication for business industries (Teru et al., 2017). An accounting information system (AIS) is defined as mix of general accounting practices with information technology sources (Investopedia, 2020). The function of accounting information system in each business is very important in handling an organization and executing an internal control system (Romney and Steinbart, 2015). ..